PENGEMBANGAN MEDIA CAPIRILI PEMBELAJARAN LEMPAR CAKRAM PADA PESERTA DIDIK SMP MUHAMMADIYAH PANGKALPINANG - Widati Amalin Ulfah; Oktarina (Jurnal Penjaskesrek, 2020)
The lack of students’ knowledge in discus throwing learning,  the lack of discus throwing facilities at school, and the lack of media usage that are appropriate with the students characters were all the background of this study conduction. The purpose of this study was to produce CAPIRILI media on discus throwing learning for students of SMP Muhammadiyah Pangkalpinang. This study used Research and Development (R & D) method from Borg and Gall development model. The population of this study were all the students with total number of 236. The samples of this study were 40 students. The data were collected by distributing questionnaire for experts namely for sport education teacher, questionnaire  for students, and documentation. The techniques of analyzing the data were in the form of interview, questionnaire for expert, and instrument for students. Based on the result of validation of material by the expert and questionnaire for the teachers, it was obtained that the average score of material expert validation was 78 percent which was on “valid” category, score of media expert validation was 84 percent which was on “very valid” category. The result of small scale try out was 83 percent which was on “very good” category. The result of large scale try out was 86 percent whic was on “very good” category too. Then, teachers’ response was 90 percent which was “ver good” category. Based on the result of expert validation and the try out, it was relvealed that CAPIRILI media was considered as a media with “very good” category and feasible to use.AbstrakPengetahuan peserta didik dalam pelaksanaan pembelajaran lempar cakram sangat minim, kurangnya sarana lempar cakram di sekolah, dan kurangnya penggunaan media yang sesuai dengan karakterisitik peserta didik. Tujuan penelitian ini menghasilkan media CAPIRILI pada pembelajaran lempar cakram peserta didik SMP Muhammadiyah Pangkalpinang. Penelitian ini menggunakan metode penelitian Research and Development (R & D) dari model pengembangan Borg and Gall. Populasi penelitian ini yaitu seluruh peserta didik yang berjumlah 236. Sampel yang digunakan berjumlah 40 peserta didik. Teknik  dan Pengumpulan data berupa angket oleh ahli yaitu guru pendidikan jasmani, instrumen peserta didik, dan dokumentasi. Teknik analisis data berupa wawancara, angket ahli, dan istrumen untuk siswa. Berdasarkan hasil validasi ahli materi dan angket guru diperoleh nilai rata-rata dan hasil perhitungan yaitu Validasi Ahli Materi  78% kategori “Valid”, Ahli Media  84% kategori “Sangat Valid”, Ahli Praktisi 84% kategori “Sangat Valid”. Hasil Uji Coba Skala  Kecil  83% kategori “Sangat Baik”, Uji Coba  Skala Besar kategori 86% “Sangat Baik”, Selanjutnya Respon Guru 90% kategori “Sangat Baik”. Berdasarkan hasil penelitian validasi ahli dan uji coba menunjukkan bahwa Media   CAPIRILI termasuk dalam kategori  “Sangat Baik” dan layak digunakan. Kata Kunci : Pengembangan Media, CAPIRILI, Lempar Cakram